Digging designer genomes. (September 2015) - Webb, Sarah
Techniques such as Gibson and Golden Gate assembly and homologous recombination in yeast allow researchers to assemble DNA sequences millions of base pairs in length. Sarah Webb investigates the challenges of constructing designer chromosomes and genomes, and their potential applications.